IL-18: a new player in immunotherapy for age-related macular degeneration?. (October 2014) - Campbell, Matthew; Doyle, Sarah; Humphries, Peter
<x xml:space="preserve">Abstract</x> Recent evidence suggests that the pro-inflammatory cytokine IL-18 may have utility as an anti-angiogenic agent in the eye. Numerous laboratories, including our own have demonstrated the ability of murine IL-18 to prevent neovascularization in the retina, choroid and cornea in pathological scenarios. Here, we summarize the potential use of IL-18 as an immunotherapy for wet age-related macular degeneration treatment, describing past and recent findings pertaining to its biological function in the eye.